2013
DOI: 10.12812/ksms.2013.15.2.113
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on relationship between symptoms of musculoskeletal disorders and amount of smartphone usage

Abstract: This study was conducted to investigate the characteristics of smartphone usage and posture of users during using smartphone. A survey was conducted for 983 smartphone users to understand the association between smartphone usage and including subjective symptoms associated with musculoskeletal disorders.Main results from the survey were as follows; 1) 18.8% of the subjects experienced musculoskeletal symptoms at least at one of body parts. Specifically, 8.1%, 5.6%, 4.1%, and 11.3% of the subjects experienced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 3 publications
1
21
0
2
Order By: Relevance
“…The results of a different study conducted in Asia with a similar survey method are from Hong Kong, where musculoskeletal disorders among smartphone users were shown to have a much higher prevalence than the Korean study conducted by Eom et al [8]. In the Hong Kong study, 70% of respondents reported having experienced neck pain (n = 1,049), 65% had shoulder pain, 46% experienced wrist and finger pain, [10]; the reasons for the difference in the study results from Korea and Hong Kong are not clear, however, there was a considerable difference in the sample size.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The results of a different study conducted in Asia with a similar survey method are from Hong Kong, where musculoskeletal disorders among smartphone users were shown to have a much higher prevalence than the Korean study conducted by Eom et al [8]. In the Hong Kong study, 70% of respondents reported having experienced neck pain (n = 1,049), 65% had shoulder pain, 46% experienced wrist and finger pain, [10]; the reasons for the difference in the study results from Korea and Hong Kong are not clear, however, there was a considerable difference in the sample size.…”
Section: Introductionmentioning
confidence: 86%
“…Musculoskeletal problems are among the most common occupational disorders in many countries and have an increasing trend [7]. An epidemiological study of 938 smartphone users conducted in the Republic of Korea found that 18.8% of smartphone users (n = 185) experienced musculoskeletal symptoms in at least one of their body parts [8]. In another Korean study involving 292 smartphone users, Kim et al [6] found the most painful body regions from smartphones use were reported to be the neck (55.8%) and shoulders (54.8 %) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Game tidak hanya dimainkan di komputer tetapi sudah bisa dimainkan di smartphone yang membuat seseorang menjadi lebih mudah dalam memainkan game online dimanapun dan kapanpun orang bisa memainkannya (Ayu & Saragih, 2016). Eom et al, (2013)…”
Section: Pendahuluanunclassified
“…Despite the advantages, it's excessive usage has had ill-effects on users. There have been reports on the symptoms of musculoskeletal disorders associated with the amount of text message and the time for daily usage of smart-phone during the study of characteristics of smart-phone usage and posture of users [40]. Smart-glasses not only help in relieving the "text neck" [15] but also overcome the inherent short-comings of a smart-phone.…”
Section: Motivationmentioning
confidence: 99%